Kompetensi Bahasa Inggris Mahasiswa Pendidikan Agama Islam - Razali Mahmud; Legiman Legiman (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2021)
The purpose of this study is to find out the strategies, barriers, and solutions for improving English language competence for PAI students from the Tarbiyah and Teacher Training Faculty of IAIN Langsa. The research method used is descriptive qualitative method. The research subjects were 12 PAI Study Program students and 3 lecturers who taught English courses at PAI Study Program. The instruments used are interviews and documentation. Data analysis was carried out by data triangulation. The results of the research are (1) Strategies to increase English competence in PAI students by applying various learning strategies to mastering the four English competencies, namely reading, speaking, writing, listening continuously, (2) As for the obstacles in improving English competence in PAI students of the FTIK IAIN Langsa faculty, namely the low English competence of students so that in the process of learning English, they are not so serious and focus on learning. and Learning facilities such as audio-visual are still very limited. The time and number of credits provided is still inadequate in the expected learning process. (3) The solution is that PAI students need to change their main set or their views in studying English courses. They must foster a sense of love and confidence in following the English learning process, from the lecturers, it is hoped that in the learning process they can apply various methods or strategies in order to apply the new strategies found. The faculty is expected to increase the quantity of learning facilities such as audio-visual and others so that the learning process is not constrained or hampered.